Numerical Simulation of Blast Vibration and Crack Forming Effect of Rock-Anchored Beam Excavation in Deep Underground Caverns - XinPing Li; JunHong Huang; Yi Luo; Qian Dong; YouHua Li; Yong Wan; TingTing Liu (Shock and Vibration)
Aiming at surrounding rock damage induced by dynamic disturbance from blasting excavation of rock-anchored beam in rock mass at moderate or far distance in underground cavern, numerical model of different linear charging density and crustal stress in underground cavern is established by adopting dynamic finite element software based on borehole layout, charging, and rock parameter of the actual situation of a certain hydropower station. Through comparison in vibration velocity, contour surface of rock mass excavation, and the crushing extent of excavated rock mass between calculation result and field monitoring, optimum linear charging density of blast hole is determined. Studies are also conducted on rock mass vibration in moderate or far distance to blasting source, the damage of surrounding rock in near-field to blasting source, and crushing degree of excavated rock mass under various in situ stress conditions. Results indicate that, within certain range of in situ stress, the blasting vibration is independent of in situ stress, while when in situ stress is increasing above certain value, the blasting vibration velocity will be increasing and the damage of surrounding rock and the crushing degree of excavated rock mass will be decreasing.